Local Culture as a Resource in Islamic Religious Education in Quran Savaty Elementary School - Ilham Hidayat, Muhammad; Palili, Sampara (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This research aims to explore how local culture is used as a resource in the implementation of Islamic Religious Education at Quran Savaty Elementary School. Using a descriptive qualitative approach with a case study method, this study reveals that the integration of local culture such as regional Islamic art, local wisdom values (siri' na pacce, sipakatau, and pangngaderreng), and religious activities with local nuances significantly strengthen the effectiveness of Islamic religious education. Programs such as tahfidz 30 juz, tahsinul qira'ah and recitation, educational outings, character building, love of mosques from an early age, and extracurricular activities are designed with a culturally based contextual approach. The results of the study show that this strategy succeeds in fostering students' love for the Qur'an and Islamic values, while strengthening their identity, spirituality, and connection to the socio-cultural environment. This learning model shows that Islamic education can develop inclusively, creatively, and still maintain noble local values.